Kepastian Hukum Kedudukan Camat sebagai PPAT Sementara (Legal Certainty of The Position Sub-district Head as Temporaly Land Deed Officer) - Irfan Iryadi (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2020)
After the enactment of Government Regulation Number 24 of 2016, the provisions regarding dual positions as civil servants become one of the substances regulated by this Government Regulation. The existence of these provisions has led to the blurring of norms over the head of sub-district’s position as temporary land deed officers in creating an authentic deed in the land sector. Based on this legal issue, this article was written with the aim of finding out the status of the head of sub-district’s position as temporary land deed officer and offering a concept that should be implemented when temporary land deed officer’s position is needed. The results showed that in Government Regulation Number 24 of 2016, there was no legal certainty in the formulation of the article as a result of the blurring of legal norms over officer assigned to the temporary land deed position. This obscurity can be seen from designation of the temporary land deed officer to the head of sub-district, where the head of sub-district is a State Administration Officer that is contrary to the land deed officer’s rules that prohibit land deed officer from being held by Civil Servants. The task of temporary land deed officer should be transferred to the head of village, since the head of village’s position has already been acknowledged and accommodated in the land deed officer’s rules as temporary land deed officer. This alternative is considered to provide more legal certainty and an ideal solution to the status of temporary land deed officer. Therefore, it is recommended to stakeholders in the land sector, on matters regarding the land deed officer, to conduct further assessment on this idea in order to be implemented in the assignment of temporary land deed officer in Indonesia. AbstrakPasca berlakunya Peraturan Pemerintah Nomor 24 Tahun 2016, aturan mengenai rangkap jabatan sebagai pegawai negeri menjadi salah satu substansi yang diatur Peraturan Pemerintah itu. Adanya ketentuan itu telah menimbulkan kekaburan norma atas kedudukan Camat sebagai PPAT Sementara dalam membuat akta otentik dibidang pertanahan. Bertolak dari isu hukum itu, artikel ini ditulis dengan tujuan untuk mengetahui status kekuatan kepastian hukum Camat sebagai PPAT Sementara dan menawarkan konsep yang seharusnya dilaksanakan dalam pemangkuan jabatan PPAT Sementara. Hasil penelitian menunjukkan bahwa dalam Peraturan Pemerintah Nomor 24 Tahun 2016 terdapat ketidakpastian hukum dalam rumusan pasalnya sebagai akibat adanya kekaburan norma hukum atas penyelenggaraan jabatan PPAT Sementara. Kekaburan itu terlihat dari penunjukan PPAT Sementara kepada Camat, dimana Camat merupakan Pejabat Tata Usaha Negara yang bertentangan dengan aturan Jabatan PPAT yang melarang PPAT diselenggarakan oleh Pegawai Negeri Sipil. Seharusnya pengembanan PPAT Sementara itu dialihkan kepada kepala desa, dimana keberadaan kepala desa itu juga diakomodasi dalam ketentuan jabatan PPAT sebagai PPAT Sementara. Hal itu dianggap lebih memberikan kepastian hukum dan merupakan solusi ideal dalam pemangkuan PPAT Sementara. Oleh sebab itu, disarankan kepada pemangku kepentingan dibidang pertanahan, khususnya di bidang PPAT agar dapat melakukan pengkajian atas gagasan ini untuk diimplementasikan terhadap pemangkuan jabatan PPAT Sementara di Indonesia.